1998
DOI: 10.1002/(sici)1521-3765(19980515)4:5<864::aid-chem864>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of Encapsulated Guests: Ferrocene inside Cram's Hemicarcerands

Abstract: The voltammetric behavior of ferrocene encapsulated inside two hemicarcerand hosts was investigated in dichloromethane and tetrachloroethane solutions. Molecular encapsulation led to substantial changes in the anodic voltammetric behavior of the ferrocene nucleus. Generally, encapsulated ferrocene exhibited a more positive halfwave oxidation potential and a lower apparent standard rate constant of heterogeneous electron transfer than uncomplexed ferrocene under identical experimental conditions. Whereas the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 34 publications
1
43
0
2
Order By: Relevance
“…A few years ago, we investigated the voltammetric behavior of Fc trapped inside a hemicarcerand and showed that the electrochemical kinetics upon encapsulation was slower than that of free Fc. 4 More recently, we have investigated the voltammetric response of Cob+ inside hexameric resorcinarene molecular capsules 5 and demonstrated that encapsulated Cob+ is voltammetrically silent. These two cases correspond to kinetically stable complexes, which are only soluble in nonpolar solvents, such as CH 2 Cl 2 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A few years ago, we investigated the voltammetric behavior of Fc trapped inside a hemicarcerand and showed that the electrochemical kinetics upon encapsulation was slower than that of free Fc. 4 More recently, we have investigated the voltammetric response of Cob+ inside hexameric resorcinarene molecular capsules 5 and demonstrated that encapsulated Cob+ is voltammetrically silent. These two cases correspond to kinetically stable complexes, which are only soluble in nonpolar solvents, such as CH 2 Cl 2 .…”
mentioning
confidence: 98%
“…In both cases, the relative attenuation of the electrochemical kinetics was rationalized by the increased distance between the encapsulated redox center and the electrode surface at the time of the heterogeneous electron-transfer event (closest approach to the electrode surface). Very recently, Sarmentero and Ballester 14 have reported the electrochemical behavior in MeOH and acetone of the guest Cob+ included in a hybrid cavitand-resorcin [4]arene structurally related to host 1. In this case, the inclusion complex shows a reversible set of waves at more negative half-wave potential than the free guest.…”
mentioning
confidence: 99%
“…We prepared two similar hemicarcerands (1 and 2) with octaimine connectivity between the two cavitand bowls and two different "feet" substituents on the polar ends: phenylethyl and pentyl. 48 Scheme 3.7 shows the structure of hemicarcerand 1 (with phenylethyl feet). The size of the equatorial portals allows the inclusion of ferrocene when guest and host are heated together in tripiperidinephosphine oxide.…”
Section: Electrochemistry Of Redox-active Hemicarceplexesmentioning
confidence: 70%
“…More interestingly, the standard rate constant for the heterogeneous electron transfer process (k o ) decreased from 0.043 to 0.0041 cm/s. 48 The data obtained with both hemicarceplexes (Fc@1 and Fc@2) in tetrachloroethane solution were entirely similar. …”
Section: Electrochemistry Of Redox-active Hemicarceplexesmentioning
confidence: 99%
“…To get more insight, Kaifer compared the electrochemical behavior of free and incarcerated ferrocene inside 26 (Figures 9.3 and 9.9 ). 25 In the inner phase, ET was strongly hindered kinetically and thermodynamically. A more positive half -way potential for the oxidation, due to the hydrophobicity of the inner phase, as well as 10 -fold rate retardation was measured.…”
Section: Electron Transfer Reactionsmentioning
confidence: 99%